2019
DOI: 10.1049/iet-epa.2018.5554
|View full text |Cite
|
Sign up to set email alerts
|

Noise reduction of axial‐flux motors by combining various pole‐arc coefficients and circumferential shifting of permanent magnets: analytical approach

Abstract: The electromagnetic noise of an axial-flux in-wheel motor (AFWM) is reduced by combining various pole-arc coefficients and circumferential shifting of permanent magnets (PMs) here. First, the analytical model of the air-gap magnetic field for the AFWM with various pole-arc coefficients and circumferential shifting of PMs is established. The influence of edging effect and stator slotting is taken into account through the radial correction function and complex relative permeance function, respectively. Subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…The optimization design combination was verified in the 3D-FEA model, and the results showed that the efficiency of AFPM motor was up to 91.5 %. Additionally, some studies used hybrid algorithms with GA to optimize the design of AFPM motors, such as a hybrid genetic algorithm (HGA) combining simulated annealing and father-offspring selection [77], the elitist genetic algorithm (EGA) [87], the non-dominated sorting genetic algorithm (NSGA-II) [88], etc.…”
Section: Optimization Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimization design combination was verified in the 3D-FEA model, and the results showed that the efficiency of AFPM motor was up to 91.5 %. Additionally, some studies used hybrid algorithms with GA to optimize the design of AFPM motors, such as a hybrid genetic algorithm (HGA) combining simulated annealing and father-offspring selection [77], the elitist genetic algorithm (EGA) [87], the non-dominated sorting genetic algorithm (NSGA-II) [88], etc.…”
Section: Optimization Designmentioning
confidence: 99%
“…The optimization design combination was verified in the 3D-FEA model, and the results showed that the efficiency of AFPM motor was up to 91.5%. Additionally, some studies used hybrid algorithms with GA to optimize the design of AFPM motors, such as a hybrid genetic algorithm (HGA) combining simulated annealing and father-offspring selection [77], the elitist genetic algorithm (EGA) [87], the non-dominated sorting genetic algorithm (NSGA-II) [88], etc. With the further development of efficient computer system and optimization theory, new multi-objective optimization algorithms such as particle swarm optimization (PSO) [89,90], bat optimization (BO) [91] and the Taguchi algorithm [92] have also been applied to the optimization design of AFPM motors.…”
Section: Optimization Designmentioning
confidence: 99%
“…6. A multiphysics modal is established according to [27]. Combining the electromagnetic force of the stator teeth calculated by JMAG with the modal results of the SRM enclosure obtained by ANSYS, the enclosure vibration response is calculated in LMS by the modal superposition method.…”
Section: Relationship Between the Vibration And The Radial Force Hamentioning
confidence: 99%
“…Moreover, the analytical model facilitates the analysis of the magnetic field under fault operating conditions, for example, misalignment and eccentricity [19,20]. It is also timesaving and efficient for the analytical model to calculate the EM forces over a wide operation range at design stage of a low vibration motor [21]. As for the structural dynamic response solution, the 3D entire structural FE model is commonly adopted to compute the vibration; because the motor structure can be roughly regarded as a cylinder, it has both circumferential and axial modes [22].…”
Section: Introductionmentioning
confidence: 99%